Design of elastomer coatings for concrete impact damage mitigation. (December 2020) - Fallon, C.; McShane, G.J.
Highlights: Elastomer coating design maps for concrete impact damage mitigation are produced. Analytical models are established to predict trends in critical impact velocity. Elastomer modulus and thickness are taken as the key design variables. The trends are accurately predicted as shown by comparison with experiment and FEA. The models reveal key parameter sensitivities for concrete protective coatings. Abstract: Practical, cost-effective strategies are of interest for the protection of vulnerable infrastructure against dynamic load events such as blast and fragment impact. Recent research has established that spray-on elastomer coatings can provide a significant impact mitigating effect when applied to concrete structural elements [1] . However, to date, no practical design guidelines exist to support efficient implementation of this retrofit solution. In this work, an analytical model is proposed for the impact indentation of an elastomer-coated concrete structural element. Design maps are produced, predicting the critical projectile impact velocities for elastomer failure and concrete failure, taking the coating thickness and elastomer modulus as the key design variables. The analytical predictions provide a close match to experimental and finite element analysis (FEA) results [1, 2] . Spanning a realistic range of elastomer moduli, representative of typical spray application polymers, a regime change is predicted that depends only on the elastomer modulus, Ee . For Ee  < 50 MPa, elastomer failure is predicted to occur first. In this regime, there is a much higher sensitivity to Ee compared with the elastomer thickness, he . For Ee  > 50 MPa, the concrete is predicted to fail first and in this regime, the critical velocities are most sensitive to he compared with Ee .